The Occupational Stress Questionnaire for Law Enforcement Services - Andrea Cecília Tegyey (Belügyi Szemle, 2025)
Aim: Motivation is an important management tool, especially in organisations where people's skills and abilities are crucial to effective performance. An example of such an organisation is the Police, which is still people-centred despite information technology modernisation. Motivation is therefore essential not only in leadership, but also in the psychological selection process, and its components and characteristics are examined.